Preparation and characterization of rice husk ash for adsorption of phenol from aqueous solutions - Daffalla, S.B. (Trans Tech Publications Ltd, 2014)
In this research, the development of three (3) low-cost adsorbent materials from abundant waste rice husk was achieved via thermal treatment. The physiochemical properties of the developed adsorbents were evaluated. Their adsorption behaviours in batch system were evaluated for the removal of phenol from aqueous solutions by varying the pH (2 to 10). It was found that, the rice husk ash burned a 400Í¦C for 1hr âRHA400,1â has the highest surface area (201.36 m2.g-1) followed by RHA300,4 (87.08 m2.g-1) and RHA600,1 (43.22 m2.g-1), respectively. RHA400,1 had shown the highest removal efficiency followed by RHA300,4 and RHA600,1, towards phenol due to high surface area and porosity. The maximum uptake of phenol was found at pH 4. The adsorption kinetics was well described by both pseudo-second order and the Elovich models. Â© 2014 Trans Tech Publications, Switzerland.